EVEKTIFITAS PEMUNGUTAN PAJAK REKLAME TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN JENEPONTO - Andi Rustam; Muh. Nur R; A. Jam'an; Firdaus Firdaus (Universitas Muhammadiyah Makassar, 2021)
This study aims to determine the effectiveness of advertisement tax collection on regional revenue at the Regional Revenue Agency of Jeneponto Regency. This research is a qualitative descriptive type of research. This research data includes primary data and secondary data. Data collection techniques using library research techniques and documentation study research. The results of the study show that the advertisement tax collection on regional revenue in Jeneponto district is effective due to the level of compliance and awareness of taxpayers in paying the advertisement tax effectively